Entrepreneurial Behaviour and Constraints Encountered by Dairy and Poultry Entrepreneurs in Jammu Division of J&K State - Bhavana Gupta , S.K. Kher ,; M.S.Nain (Indian Journal of Extension Education, 2013)
The investigation on 60 entrepreneurs, thirty each selected from dairy and poultry entrepreneurs from Jammu and Kathua districts or J & K state revealed that majority of the entrepreneurs had medium level of achievement motivation, risk taking behaviour, decision making ability, communication skills, adoption propensity and self confidence. Poultry entrepreneurs had more internal locus of control than dairy entrepreneurs. Overall entrepreneurial behaviour index was high in case of poultry entrepreneurs. The major constraints identified in case of dairy entrepreneurs were high initial investments (80%), costly veterinary medicines and treatment (66.66%), frequent prevalence of diseases (63%), lack of storage facilities (60%) and lack of knowledge about balanced diet (53%). In case of poultry entrepreneurs, high mortality rate (73.33%), high cost of good quality feed (60%), difficulty in borrowing loans (53.33%), lack of technical guidance (50%) and lack of knowledge about causes and treatment of diseases (46.66%) were the major constraints reported by the entrepreneurs.